Shared Solitude. Issue 1 (June 2021) - Khemka, Anita; Kokiloo, Imran
Shared Solitude was born out of a literal and forced isolation as a result of a family emergency, coinciding with the very unplanned and brutal lockdown, enforced by a political system hell-bent on being seen as decisive. It made us question the status quo we had grown accustomed to and the dichotomy of our daily lives. One of our early sitters, Ishita echoed our views, 'Living in lockdown has been a revelation. I have realized that [certain] relationships, having time to read, being with dogs, and having enough meaningful work in the day is enough for me—this is all I would like to keep in my life'. This burgeoning clarity and purpose about one's life, we realized, was shared by many people. This project thus set out to excavate memory, the joyous and painful, and confronts the universal dilemma of ownership, possession and letting go.